2014
DOI: 10.1091/mbc.e13-02-0110
|View full text |Cite
|
Sign up to set email alerts
|

CHES1/FOXN3 regulates cell proliferation by repressing PIM2 and protein biosynthesis

Abstract: CHES1/FOXN3 inhibits cell proliferation and protein biosynthesis in tumor cell lines but not in normal fibroblasts. CHES1 directly represses the expression of the gene coding for the protein kinase PIM2, and PIM2 or eIF4E counteracts the antiproliferative effect of CHES1. The levels of CHES1 and PIM2 are inversely correlated in several human cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 39 publications
0
30
1
Order By: Relevance
“…FOXN3 is a direct target of and is downregulated by miR-574-5p to promote the progression of human lung cancer [18]. Moreover, FOXN3 inhibits cell proliferation by repressing PIM2 and protein biosynthesis [19]. FOXN3 also suppresses the expression of N-cadherin mRNA and protein by transcriptionally repressing N-cadherin promoter activity [20].…”
Section: Discussionmentioning
confidence: 99%
“…FOXN3 is a direct target of and is downregulated by miR-574-5p to promote the progression of human lung cancer [18]. Moreover, FOXN3 inhibits cell proliferation by repressing PIM2 and protein biosynthesis [19]. FOXN3 also suppresses the expression of N-cadherin mRNA and protein by transcriptionally repressing N-cadherin promoter activity [20].…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, FOXN3 was described as a checkpoint suppressor (CHES1) in yeast (5) and was shown to inhibit protein biosynthesis (6) or to downregulate E2F5 in human cells to control cell cycle (7). At the molecular level, although it has been reported that FOXN3 interacts with xSin3/xRPD3 in X. laevis (3) and Sin3 in Saccharomyces cerevisiae (8) and with MEN1 (9) or SKIP (10) in human cells to exert transcriptional repressive function, in Drosophila testes it was demonstrated that FOXN3 acts to activate transcription (11).…”
Section: Introductionmentioning
confidence: 99%
“…The data from human protein atlas (http://www.proteinatlas.org/) revealed that the protein levels of FOXN3 were upregulated in most cancer tissues. A recent study in a cancer cell line indicated that CHES1/FOXN3 decreases cell proliferation by repressing PIM2 and protein biosynthesis, suggesting that FOXN3 is a potential tumor suppressor [38]. However, we found that overexpression of CHES-1-like in fly testis could prevent early germ cell differentiation and lead to tumor-like structure formation.…”
Section: Discussionmentioning
confidence: 58%